2018
DOI: 10.1155/2018/4069032
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Promote the Osteogenesis in Collagen-Induced Arthritic Mice through the Inhibition of TNF-α

Abstract: Objective To investigate the effects of umbilical cord mesenchymal stem cell (UC-MSC) transplantation on joint damage and osteoporosis in collagen-induced arthritis (CIA) mice and to explore the mechanisms by which UC-MSCs modulate the osteogenic differentiation. Methods CIA mice were divided into the following treated groups: UC-MSC transplantation group, antitumor necrosis factor- (TNF-) α group, and zoledronic acid (ZA) group. Microcomputed tomography (micro-CT) was used to analyze the bone morphology param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…Previous studies have shown inflammation has a significant correlation with osteogenic differentiation . Nevertheless, the precise molecular basis has not been presented up to date.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies have shown inflammation has a significant correlation with osteogenic differentiation . Nevertheless, the precise molecular basis has not been presented up to date.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown inflammation has a significant correlation with osteogenic differentiation. [18][19][20] Nevertheless, the precise molecular basis has not been presented up to date. In the current study, we first examined the regulatory role of the primary inflammatory signalling NF-κB in osteogenesis, using gain or loss of NF-κB function experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 The activation of NF-κB can restrain osteogenesis. [22][23][24] However, the molecular basis by which NF-κB inhibits osteogenic differentiation is still unclear until now.…”
Section: Discussionmentioning
confidence: 99%